Pelatihan Intensif Metode UMMI Dalam Meningkatkan Kualitas Pengajaran Guru Al-Qur’an Di Desa Pisang Kecamatan - Mastur, Mastur; Indramawan, Anik; Yuli Dianto, Alfin; Fitrotus S, Dewi (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2022)
The important role of teachers in educational institutions includes the Al-Qur'an Education Institution (TPQ), as well as the demand for teachers to have the capacity and capability in learning the Qur'an. So the researchers took the initiative to solve the problem using the PAR (Participatory Action Research) method. The focus of this assistance is the UMMI Method of Al-Qur'an Teacher Training Procedures and how the impact of the UMMI Method of Al-Qur'an teacher training in Pisang village. The results of this assistance are First, the increasing awareness of TPQ teachers about the importance of the teaching methods used in the process of teaching reading and writing the Qur'an. For example, with the application of 4 models of learning Al-Qur'an, the UMMI Method which includes: private/individual, individual classical, classical reading and listening, and classical reading and listening purely, can improve students' skills in reading and writing the Qur'an quickly and easily. dynamic. Second, the growing fighting spirit of the TPQ teachers in teaching their students using the UMMI method. The application and implementation of the UMMI Method in the Al-Quran learning process at assisted TPQs is guided by the program and learning stages that have been set by the UMMI Foundation. Among them; Implementation of the 7 Basic Ummi Method Programs which include: Tashih, Tahsin, Teacher Certification, Coaching, Supervision, Munaqasah, and Khataman.